Caught in the middle? How voters react to spatial indifference. (October 2021) - Rodon, Toni
Abstract: According to one of the tenets of the Spatial Theory of Voting (SToV), spatial indifference is positively associated with abstention. However, the political behaviour literature has not yet fully settled whether this is always the case and, if not, why individuals still vote despite the differential utility they extract from the two closest candidates equals zero. In this letter we explore the effect of spatial indifference on political behaviour by analysing survey data from American elections since 1972 and through a survey experiment that randomizes candidates' ideological position on different dimensions. Findings show that spatially indifferent individuals are more likely to abstain—mainly moderate voters. Yet, around two-thirds still vote for a candidate. We advance two tentative explanations: First, when spatially equidistant, individuals that vote are more likely to consider valence attributes. Second, they are more likely to resort to a directional logic. Results have implications for our understanding of the spatial models and, in particular, of the behaviour of spatially equidistant individuals, which represent a non-negligible group of the electorate.